LEPTIN A19G POLYMORPHISM AND LEPTIN RECEPTOR Gln223Arg AND Lys109Arg POLYMORPHISMSIN POSTMENOPAUSAL OSTEOPOROSIS - Mikhail Yur'evich Krylov; L I Benevolenskaya; V A Myakotkin; Mikhail Yuryevich Krylov; L I Benevolenskaya; V A Myakotkin (Научно-практическая ревматология, 2010)
Objective: to study an association of leptin (LEP) A19G polymorphism and leptin receptor (LEPR) Gln223Arg AND Lys109Arg polymorphisms with the predilection for postmenopausal osteoporosis (OP). Subjects and methods. PCR analysis was used to examine the polymorphisms among 428 women (254 patients with OP and 174 healthy women). The anthropometric, densitometric, and biochemical markers of bone remodeling and standard clinical and biochemical parameters were studied. Results. Statistically significant differences were found in the distribution of the genotypes of LEP A19G polymorphism between the women with OP and the controls (χ2 = 9.41; p = 0.009). In the patients with OP, the 19GG genotype frequency was significantly higher than that in the controls [OR = 2.0; 95% confidence interval (CI) 1.13-3.52 (p = 0.011)]. LEP 19GG genotype carriers were found to have lower mineral bone density (MBD) of the femoral neck than heterozygotes (p = 0.06). In LEPR 223GlnArg heterozygotes, the mean MBD of the trochanter and whole hip was statistically significantly lower than that in patients with the genotype 223ArgArg (p = 0.013). 223GlnGln carriers were taller than 223GlnArg ones (p = 0.04). There were no associations of the clinical and biochemical parameters with the polymorphisms studied. Conclusion. Our study confirmed the role of LEP A19G and LEPR Gln223Arg polymorphisms as important candidate genes involved in the formation of a predilection for OP.